THE DISCOURSE OF PHENOMENOLOGICAL MUSICAL EDUCATION: BETWEEN ETHICS AND AESTHETICS - Venslovaitė, Vita (Acta Paedagogica Vilnensia, 2011)
The article describes the concepts of musical education in the historical context and uncovers the reasons due to which the problems of the value of the musical education have arisen. The approach of various philosophical schools’ representatives – Aristotle, I. Kant, A. Schopenhauer, F. Nietzsche as well as education specialists T. Clifton and D. E. Denton towards music and its practical application in the educational process is presented. The article points out how this approach had varied depending on the perception of art and ethical and aesthetic attitudes that existed in the era of a philosopher or education specialist.The article examines the possibility to apply the phenomenological method in the education process. The particularity of the phenomenological method and its suitability for the musical education is highlighted. While explaining this method, it is sought to give a sense to the musical education emphasizing its significance and value.Pursuant to the paradigm of the phenomenological education, which states that education helps to reveal all the possibilities of an individual’s self-expression and that such revelation of the possibilities must not overstep the limits which would violate the space of another person, it is shown that essentially any form of the phenomenological education, including the musical education as well, is based on the ethical attitude. The musical education, as well as the development of aesthetic education, is both ethical and aesthetical in the phenomenological education.
Keywords: Musical education; music; aesthetic perception; ethics; phenomenology